2016
DOI: 10.1128/mbio.02210-15
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Attenuates Trimethylamine- N -Oxide (TMAO)-Induced Atherosclerosis by Regulating TMAO Synthesis and Bile Acid Metabolism via Remodeling of the Gut Microbiota

Abstract: The gut microbiota is found to be strongly associated with atherosclerosis (AS). Resveratrol (RSV) is a natural phytoalexin with anti-AS effects; however, its mechanisms of action remain unclear. Therefore, we sought to determine whether the anti-AS effects of RSV were related to changes in the gut microbiota. We found that RSV attenuated trimethylamine-N-oxide (TMAO)-induced AS in ApoE−/− mice. Meanwhile, RSV decreased TMAO levels by inhibiting commensal microbial trimethylamine (TMA) production via gut micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
510
4
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 616 publications
(542 citation statements)
references
References 49 publications
23
510
4
5
Order By: Relevance
“…We confirmed previously detected associations between TMAO and the abundance of Peptococcaceae ( P  = 4.67 × 10 −4 ) and Prevotella ( P  = 0.004) (Fig. 2) [12, 35]. Interestingly, we also observed a negative association between TMAO and the abundance of common gut commensal Faecalibacterium prausnitzii ( P  = 0.006; FDR <0.08).…”
Section: Resultssupporting
confidence: 90%
“…We confirmed previously detected associations between TMAO and the abundance of Peptococcaceae ( P  = 4.67 × 10 −4 ) and Prevotella ( P  = 0.004) (Fig. 2) [12, 35]. Interestingly, we also observed a negative association between TMAO and the abundance of common gut commensal Faecalibacterium prausnitzii ( P  = 0.006; FDR <0.08).…”
Section: Resultssupporting
confidence: 90%
“…Therefore, the changes in urinary amino acids and derivatives revealed by the metabolomic analysis may imply a resveratrol-induced modulation of the gut flora in men with metabolic syndrome. This is in accordance with studies in rodents where resveratrol has been shown to modulate the gut microbiota directly [41,42,43]. …”
Section: Discussionsupporting
confidence: 92%
“…Treatment with RSV resulted in an increase in Bacteroidetes abundance at the expense of Firmicutes in choline-treated apoE −/− mice. Serum TMA and TMAO levels were much lower in RSV-treated mice fed with choline than in those in the control group [55]. …”
Section: Therapeutic Strategiesmentioning
confidence: 99%